How do different laboratory environments influence students' attitudes toward science courses and laboratories? - Kapici, Hasan Ozgur; Akcay, Hakan; de Jong, Ton (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
The science learning environment is an important factor in students' attitudes toward their science experiences in school, as well as toward science courses. This study compares how learning in different laboratory environments (hands-on or virtual) influences these attitudes for middle school (7th grade) students. Participants were 143 seventh-grade students from a public school. They were enrolled in four different seventh-grade science classes, all taught by a single teacher. Pretest and post-test responses were compared to investigate participants' attitudes toward different forms of laboratories and toward science courses. Data were gathered by giving students an attitude questionnaire (pretest and post-test) and by conducting interviews (post-test). Findings revealed that laboratory experiences have a strong impact on middle school students' attitudes toward science; after working with the laboratory environment (either hands-on, virtual, or in a combination) students had a more positive attitude toward science. Data based on the questionnaire revealed no differences in attitudinal improvement between hands-on, virtual, or combinations of these labs, although descriptive data suggested that virtual labs are more effective for attitude change than hands-on labs. This may be linked to students' overall, but slight, preference for virtual laboratories over hands-on laboratories, as became apparent from the interviews.
Keywords: Hands-on laboratory; virtual laboratory; attitudes toward science; learning environment; middle school student; INQUIRY-BASED SCIENCE; COMPUTER-SIMULATIONS; PHYSICAL MANIPULATIVES; VIRTUAL MANIPULATIVES; ACHIEVEMENT; INSTRUCTION; EDUCATION; MOTIVATION; TEACHERS; IMPACT; Education & Educational Research